An empirical mathematical model to select the best controller in software-defined networks infrastructure - Taima, Alaa; Hilal, Osama Majeed; Al-Shammari, Ahmed Mohammed; Naseriparsa, Mehdi (Al-Qadisiyah journal for engineering science, 2025)
Software Defined Networks (SDNs) are one of the most important modern technologies in the field of networks, because of their advantages in the architecture and management of networks and control of their full functionality. SDN is distinguished from traditional networks by the presence of a central control element, which is the controller that is responsible for all operations that occur in the network. The controller is the main element that determines the success or failure of software-defined networks, so it was necessary to study and compare the different types of controllers that exist today. This paper proposes an empirical mathematical model to choose the best controller for SDN by using a Mininet emulator, concerning two performance metrics (Throughput and latency) for diverse parameters such as different types of topologies, diverse numbers of hosts, diverse numbers of switches, and diverse numbers of threads. These performance metrics have different weights depending on the needs of the users. We employ OpenFlow as a southbound protocol and five SDN controllers (Ryu, POX, OpenDaylight (ODL), and Floodlight). The results demonstrate that the suggested mathematical model is effective and flexible in choosing the best controller since the weights of performance measures are selected based on the needs of the user. The performance of the SDN network is better with ODL than with other SDN controllers.